2014
DOI: 10.1080/14786435.2014.961585
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale investigation of grain boundary structure role on intergranular deformation in aluminium

Abstract: The role that grain boundary (GB) structure plays on the plasticity of interfaces with preexisting cracks and on the interface crack dynamics was investigated using molecular dynamics for both <100> and <110> aluminum symmetric tilt grain boundaries (STGBs). In simulations with a crack at the interface, this research shows how the maximum normal strength of the interface correlates with the respective GB energy, the GB misorientation, and the GB structural description. For instance, the normal interface streng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…Research has shown that both the macroscopic degrees of freedom and microscopic local structure affect the physical properties of grain boundaries. [5][6][7][8][9][10][11] In terms of the microscopic local structure, the translations between adjoining grains are also important, as is the localized dislocation structure of the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that both the macroscopic degrees of freedom and microscopic local structure affect the physical properties of grain boundaries. [5][6][7][8][9][10][11] In terms of the microscopic local structure, the translations between adjoining grains are also important, as is the localized dislocation structure of the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The term structural unit (SU) has been used to describe the local atomic arrangement at the grain boundary and is associated with both the grain boundary character and its properties (e.g. [9,[28][29][30][31][32]). Experimentally, Saylor et al [33] studied the grain boundary character distribution (GBCD) as a function of grain boundary geometry for a commercially pure Al sample.…”
Section: Introductionmentioning
confidence: 99%
“…Because the mechanical behavior and fracture of polycrystalline materials is often driven by grain boundaries and their underlying structure [2][3][4], a fundamental understanding of the relationship between the grain boundary structure and associated properties is important to develop interface-dominant materials. Research has shown that both the macroscopic degrees of freedom and microscopic local structure affect the physical properties of grain boundaries [5][6][7][8][9][10][11][12]. The term grain boundary character is often used to describe the five degrees of freedom necessary to define a grain boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported that smaller grain boundaries will make the metal harder and stronger [10]. In the smaller grain, there is one square unit of grain boundary for each dislocation.…”
Section: Heat Treated T5 137mentioning
confidence: 99%